„Вторая” жизнь советских комедий в интернет-мемах периода пандемии - Wilk, Gabriela (Studia Rossica Posnaniensia, 2022)
Nowadays, it is hard to imagine internet culture without memes. To achieve a humorous effect, meme creators use various means, displaying unprecedented creativity. They often draw inspiration from cult Soviet comedies by Leonid Gaidai, Georgiy Daneliya, Vladimir Menshov, Eldar Ryazanov, Aleksandr Sery and other famous directors. This article is devoted to the analysis of iintertextual connections in Russian internet memes related to the current COVID-19 pandemic. The intertextual references can be in the form of a frame from a Soviet comedy, a movie catchphrase, or both at the same time. Catchphrases can be used in the analysed internet memes in their original version, or they can undergo various modifications, such as the replacement of some components and/or the extension of phrase composition. The fact of making use of a specific movie scene or catchphrase by meme creators proves that Soviet comedy is still deeply rooted in Russian culture. Soviet comedies begin to “live a new life” in internet memes.